Natureza e sagrado na memória da festa de Bom Jesus dos Navegantes - Corrêa, Isabella Cristina Chagas (2013)
Visions of nature establish different relationships between man and the natural world. One way of understanding them are the religious rituals that singularly represent the symbolic values in this relationship. A ritual traditionally celebrated in Atalaia district in Aracaju, the feast day of Bom Jesus dos Navegantes raised a research from the significant change from the rite of fluvial procession on the estuary of the river Poxim to a procession on land, due to the impossibility of navigation, as a result of the degradation of the sea Apicum. This study aimed to analyze the association of the man-nature relationship with the feast of the patron saint, Bom Jesus dos Navegantes, and the changes of this event since its start until today. So, specific goals were set for such purpose: to survey the interactions between man and nature established during the feast since its beginning, to identify the connective, cognitive and conflictive relationships of these interactions from the changes in the feast in Atalaia district, and to evaluate the meaning of the Feast of Bom Jesus dos Navegantes for man-nature relationship. This qualitative research used the oral history as a methodology. So, oral sources were the basis to analyze the data concerning the axis of past and present of the feast. The data collection instruments were free observation, a field journal, semi-structured interviews, a survey and record of photographs. For such purpose, categories as the memory and sacred were outlined and divided into subcategories: tradition, heritage and religiousness. Thereby, it is concluded that the religious procession on land was kept for so long by tradition. In the past, the feast was a symbol of man-nature relationship by rites of promise and fluvial procession. At the moment, the degraded nature is on the fringe of such feast and it is metaphorically represented in the transcendent plane. Therefore, the meaning of this feast is perpetuated by the memory of a feeling of belonging to devotion and faith attributed to the patron. Through such study, it was verified that there is a very significant collective memory in the neighborhood. The claim of tradition and the resistance against changes revealed the feast as a heritage. Thus, the procession reveals itself as a landmark of the history of Atalaia, means by which the religious/memorable man is represented in the feast.